Defining crash configurations for Powered Two-Wheelers: Comparing ISO 13232 to recent in-depth crash data from Germany, India and China. (March 2021) - Puthan, Pradeep; Lubbe, Nils; Shaikh, Junaid; Sui, Bo; Davidsson, Johan
Highlights: We studied Powered Two-Wheeler crashes with seriously injured riders. We analyzed 1824 crashes from GIDAS, 662 from RASSI and 321 from CIDAS. Cars were a common collision partner in all countries, but trucks dominated in India. Impact points, angles, and speeds are described in detail. ISO 13232 crash scenarios do not represent the most common crashes in our data. Abstract: The motorcyclist safety standard ISO 13232, based on crash data from Europe and the USA from the 1970s, still sets the direction for the development and evaluation of protective measures today. However, it is unclear how relevant the crash configurations in the standard are to present-day motorcycle crashes in Europe, the USA and other parts of the world. We analyzed recent in-depth crash data from Germany, India and China, examining powered two-wheeler (PTW) crash configurations in which at least one police-reported serious injury was present. After assessing the relevance of the ISO's PTW crash configurations to those we found in each country, we suggested new configurations to guide the development of safety systems that would be more effective at reducing PTW-related fatalities and serious injuries. In all three databases, passenger cars were among the top two most frequent collision partners and a car front impacting the side of the PTW was the most common configuration. Notably, although collisions with trucks constituted the most common scenario in India and ground impact (primary collision) was a common scenario in both Germany and India, the ISO did not include either configuration. Further, in three of the seven ISO crash configurations, one of the collision partners is stationary, although stationary collision partners were rare in our data. Our results show that the ISO crash configurations do not represent the most frequent PTW road crashes in Germany, India or China. However, the Chinese database was confined to crashes with a collision partner with four or more wheels. Further, weighting factors for these data were not available, so we could not extrapolate the frequency of the Chinese crash configurations across the entire population. A revised version of the ISO could serve as a basis for a full-scale PTW crash test program. However, the observed differences between countries imply that a single global standard may not be feasible. To optimize the evaluation of a PTW safety system, we recommend the inclusion of configurations which are frequent in the region or country of interest—in addition to common configurations occurring frequently all around the world.